A Need Analysis in English Literature Contents Among High School Teacher and Students in Yogyakarta - Hazairin Eko, Prasetyo; Adhi, Kusuma; Victa Sari Dwi, Kurniati (Diksa : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2021)
The research was carried out to find out how English high school teachers and students in Yogyakarta needed English literature contents in the teaching of English language to support the development of character educational values among the students. The approach of the research was quantitative in nature. The research was held at five senior high schools organizing special interest classes in foreign languages including English. Twenty-two (22) teachers and fifty-nine (59) students were involved in this research as respondents. The instrument for collecting data consisted of questionnaires which asked questions about the necessities, lacks, and wants (Nation & Macalister, 2010) in using literary materials or contents to support character educational values development in the students. The questionnaires items applied Likert Scale response model. The responses were analyzed by using frequency distribution and proportionality technique in percentage. The results of the analysis were presented in the forms of graphs and tables and showed that both the teachers (92.51%) and students (85.77%) needed English literature contents in their learning of English language to support the development of character educational values among the students. Moreover, both the teachers (97.16%) and students (71.55%) had very high expectations about the resourcefulness of literature contents in delivering English language lessons to support the development of particular character educational values among the students.